Increased sensitivity to the acute effects of MDMA ("ecstasy") in female rats - Palenicek, T; Votava, M; Bubenikova, V; Horacek, J (Physiology & behavior, 2005)
Behavioral effects of +/-3,4-methylenedioxymethamphetamine (MDMA, ecstasy) are relatively well described in humans as well as in animals. However, little is known about gender differences to the effects of MDMA. The aim of our study was to evaluate gender differences in stimulant effects of MDMA (2.5, 5.0, and 10.0 mg/kg subcutaneously (s.c.)) in male and female Wistar rats. We have used three behavioral methods (activity cage, open field, and elevated plus-maze) each describing a different pattern of spontaneous behavior. In the activity cage, 30 min after the MDMA administration, horizontal and vertical locomotor activities were registered for a period of 3 min. In the open field test rats were placed into an arena 15 min after drug treatment and locomotor activity was registered for a period of 30 min. Finally, in the elevated plus-maze test, rats were given MDMA 30 min prior to measurements and subsequently they were tested in the maze for a period of 5 min. In our experiments we observed a dose-dependent locomotion-enhancing effect of MDMA both in male and female rats in both locomotor tests. Female rats were more sensitive to the locomotor-stimulating effect than males in both tests, suggesting higher sensitivity to the stimulatory effect of MDMA. Further on, MDMA increased thigmotaxis in female rats in the open field test and decreased "anxious-like" behavior in the elevated plus-maze in both genders. In conclusion, we observed higher sensitivity of females to the locomotor-stimulant effect of MDMA. Increased sensitivity of females to the behavioral effects of MDMA can be explained by increased reactivity of serotonergic and dopaminergic systems.
Keywords: pátrací chování; pohybová aktivita; chování zvířat; Maze Learning; úzkost; bludiště - učení; Dose-Response Relationship, Drug; Female; N-Methyl-3,4-methylenedioxyamphetamine; N-methyl-3,4-methylendioxyamfetamin; krysa rodu Rattus; zvířata; Exploratory Behavior; Anxiety; potkani Wistar; Serotonin Agents; ženské pohlaví; Rats, Wistar; Male; Sex Characteristics; pohlavní dimorfismus; Rats; vztah mezi dávkou a účinkem léčiva; Motor Activity; Animals; mužské pohlaví; serotoninové látky; Behavior, Animal